Feasibility trial of a new digital training package to enhance primary care practitioners’ communication of clinical empathy and realistic optimism - Felicity Bishop; Jeremy Howick; Jane Vennik; Jennifer Bostock; Paul Little; Christian Mallen; Leanne Morrison; Mary Steele; Beth Stuart; Stephanie Hughes; Kirsten Smith; Mohana Ratnapalan; et al. (PLoS ONE, 2025)
Background Patients can benefit when primary care practitioners communicate clinical empathy and optimism during consultations, but previous training interventions for practitioners are overly time-consuming and evidence on patient outcomes is limited. This study assessed the feasibility of a cluster-randomized controlled trial in UK general practice to evaluate effects of a new brief digital learning package in empathy and optimism (EMPathicO) for primary care practitioners. Methods The study ran January to October 2020, with COVID-19 related modifications (mostly, practitioner and patient data had to be collected separately) from March 2020. 9 practices and 12 primary care practitioners recruited from UK (Southern England, Midlands). 12 practitioners completed EMPathicO training and 11 completed qualitative telephone interviews. Patients recruited through social media completed web-based questionnaires at baseline (<2 weeks post-consultation) and 2-week follow-up (n = 437). Purposively sampled patients completed qualitative telephone interviews (n = 30). Data analysed descriptively and thematically. Results Practitioners were keen to reflect on and enhance communication skills and were willing to undertake digital training, even during COVID-19 pandemic. However, some practices and practitioners would have declined if video-recording consultations was a mandatory aid to reflection during training. Practitioners found EMPathicO brief, relevant and engaging and could implement techniques taught in the training. Patients found the online questionnaires acceptable, though retention was suboptimal at 57%; minor easily remedied feasibility and process issues were identified (including incentivizing participation); and patients were enthusiastic about research to improve communication. Conclusions An agile research strategy enabled useful feasibility data to be collected despite the challenges of the COVID pandemic. It is feasible to proceed to a full trial of the effects of EMPathicO on patient outcomes in primary care, if video-recording consultations is optional not mandatory. Feasibility work to develop and test sophisticated questionnaire structures is valuable when planning primary care patient surveys. Registration: ISRCTN21215037. Registered: 06/02/2020. https://doi.org/10.1186/ISRCTN21215037